Learning towards enabling work-family life balance for female professionals in Ghanaian organizations / Majoreen Aryeetey, Frank Yaw Yeboah, Mohammed-Aminu Sanda - Aryeetey, Majoreen; Yaw Yeboah, Frank Yeboah; Sanda, Mohammed-Aminu (2011)
The purpose of this study is to identify the challenges inhibiting professional female employees from maintaining good work-life balances, and also to develop a framework that organizations can use to understand such gender-oriented challenges towards the design of alternative work arrangements to enhance the retention of professional female employees. An exploratory approach was used with data collected through a survey. The study revealed that conflicts between work and non-work obligations, such as family responsibilities, are sources of stress which could motivate professional female employees to quit their jobs. Flextime, compressed workweeks and telecommuting were also identified as the most preferred types of alternative work arrangements. It is concluded that many professional female employees in Ghana have knowledge of work flexibility initiatives, such as alternative work arrangements, but these are not practiced effectively in their organizations. It is recommended that organizations adopt appropriate alternative work arrangements as a motivational tool to help retain their professional female employees, not only to improve the quality of their work-life balance, but also to enhance their productivity in their organizations.